Castleman's Disease: An Intrapulmonary Form with Intrafissural Development - Hajer Racil; Sana Cheikh Rouhou; Olfa Ismail; Saoussen Hantous-Zannad; Nawel Chaouch; Mourad Zarrouk; Belhassen Smati; Faouzi Mezni; Abdellatif Chabbou (The Scientific World Journal)
Castleman's disease (CD) is an uncommon, mainly benign, lymphoproliferative disorder of unknown etiology, mostly involving the mediastinum. Parenchymal lung involvement of the disease is exceedingly rare. We describe a case of CD in a 23-year-old woman with a 4-year history of recurring dyspnea and nonproductive cough, whose chest X-ray showed an abnormal shadow of the right hilum. Chest computed tomography confirmed the presence of a tissue-density mass of the right lower lobe, demonstrating poor contrast enhancement, associated with multiple laterotracheal and mediastinal lymphadenopathies. The patient underwent curative surgery, revealing a right hilar compressive mass, with an intrafissural development between the superior and middle lobes. Pneumonectomy was performed due to profuse bleeding. This case of CD is particular because of its unusual intrapulmonary location and its intrafissural development. Poor contrast enhancement is atypical in CD.